RNAi as a management tool for the western corn rootworm, Diabrotica virgifera virgifera. Issue 9 (27th June 2016) - Fishilevich, Elane; Vélez, Ana M; Storer, Nicholas P; Li, Huarong; Bowling, Andrew J; Rangasamy, Murugesan; Worden, Sarah E; Narva, Kenneth E; Siegfried, Blair D
Abstract: The western corn rootworm (WCR), Diabrotica virgifera virgifera, is the most important pest of corn in the US Corn Belt. Economic estimates indicate that costs of control and yield loss associated with WCR damage exceed US 1 billion annually. Historically, corn rootworm management has been extremely difficult because of its ability to evolve resistance to both chemical insecticides and cultural control practices. Since 2003, the only novel commercialized developments in rootworm management have been transgenic plants expressing Bt insecticidal proteins. Four transgenic insecticidal proteins are currently registered for rootworm management, and field resistance to proteins from the Cry3 family highlights the importance of developing traits with new modes of action. One of the newest approaches for controlling rootworm pests involves RNA interference (RNAi). This review describes the current understanding of the RNAi mechanisms in WCR and the use of this technology for WCR management. Further, the review addresses ecological risk assessment of RNAi and insect resistance management of RNAi for corn rootworm. © 2016 Society of Chemical Industry